Eastern Enlargement of the EU: A Comprehensive Welfare Assessment - Wilhelm Kohler (Johannes Kepler University of Linz, Department of Economics, 2003)
This paper takes a welfare-view on eastern enlargement of the EU, focusing on incumbent countries. Enlargement is decomposed into three elements: Single-market integration on commodity markets, budgetary costs from EU-expenditure policies, and single-market-induced migration from new to present member countries. I first use an analytical model to derive a welfare equation that identifies the principle channels for incumbent country welfare gains and losses from enlargement, including product differentiation, capital accumulation, and unemployment due to search-costs. I then propose a method that allows to extend welfare results obtained from a detailed calibrated version of this model for Germany to other incumbent countries. The approach relies on model elasticities extracted from the German model which are then applied to other countries' idiosyncratic enlargement-shocks. Constructing detailed indices for such country-specific enlargement shocks, I arrive at a characteristic inter-country pattern of enlargement-induced welfare effects for all EU15 countries. Aggregating these across countries reveals enlargement to be beneficial for the union as a whole, although several countries stand to suffer welfare losses.
Keywords: 330; EU-Erweiterung; Wohlfahrtsanalyse; Allgemeines Gleichgewicht; EU-Binnenmarkt; Öffentlicher Haushalt; Internationale Arbeitsmobilität; Theorie; EU-Staaten; Osteuropa